2013
DOI: 10.1017/jns.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

Maternal long-chain PUFA supplementation during protein deficiency improves brain fatty acid accretion in rat pups by altering the milk fatty acid composition of the dam

Abstract: Long-chain PUFA (LC-PUFA) are important for fetal and neonatal brain development. However, their accretion in the brain is compromised during maternal protein restriction. Hence, we investigated the effect of maternal supplementation with n-3 DHA plus n-6 arachidonic acid (ARA) at a low protein level (9 %) on offspring brain fatty acid accretion using Wistar rats (nine rats per group) randomly fed a control (C), a low-protein (LP) or a low-protein DHA + ARA-supplemented (LPS) diet during gestation and lactatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…A recent study in rats showed that protein malnutrition compromises brain DHA, and that brain DHA can be improved by increasing DHA in rat milk (5). If these results apply to humans the importance of nutritional DHA support via reduced LA and/or supplemental DHA are all the more critical.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in rats showed that protein malnutrition compromises brain DHA, and that brain DHA can be improved by increasing DHA in rat milk (5). If these results apply to humans the importance of nutritional DHA support via reduced LA and/or supplemental DHA are all the more critical.…”
Section: Discussionmentioning
confidence: 99%
“…La placenta transfiere principalmente ácidos grasos poliinsaturados de cadena larga de la serie n-3 y n-6 (AGPICL) fisiológicamente importantes (1), y durante las primeras etapas de vida la leche materna constituye la fuente exclusiva del ácido docosahexaenoico (C22:6 n-3, DHA), de especial importancia para lograr un óptimo desarrollo neurológico (2) puesto que el feto y el neonato tienen limitada capacidad para sintetizarlo (3). Los requerimientos de lípidos durante la gestación y lactancia determinan procesos de adaptación metabólica como el incremento de las reservas grasas en el tejido adiposo y la participación de tejidos extrahepáticos (4).…”
Section: Introductionunclassified
“…Estudios en ratas hembras y mujeres señalan que la suplementación con ácido eicosapentaenoico (C20:5 n-3, EPA) y DHA incrementa la concentración de estos AGPICL en la leche materna (3,8,9). No obstante, existe información divergente al suplementar con ácido α linolénico (C18:3 n-3, ALA): Francois, et al (10) señalan que la suplementación con aceite de linaza, rico en ALA, (53.6% de ácidos grasos del perfil lipídico) aumenta la concentración de este ácido graso y de EPA, sin efecto sobre la síntesis de DHA.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In the Journal of Nutritional Science , Ranade & Rao ( 1 ) present an animal study of importance for nutritional situations in which protein is in short supply. They consider whether preformed DHA and arachidonic acid (ARA) in the dam's diet modify the effects of a low-protein diet on the DHA status of the rat pup brain.…”
mentioning
confidence: 99%